Plato's Phaedrus - Plato, (Cambridge University Press, 1997)
The dialogue begins with a playful discussion of erotic passion, then extends the theme to consider the nature of inspiration, love and knowledge. The centerpiece is the myth of the charioteer - the famous and moving account of the vision, fall and incarnation of the soul. Professor Hackforth here translates the dialogue for the student and general reader. There is a running commentary on the course of the argument and the meaning of the key Greek terms, and a full intoduction to explain the philosophical background and the place of this work among Plato's writings.